Women, work and transport - Wright, Tessa; Budd, Lucy; Ison, Stephen (Emerald Publishing Limited, 2022)
Women play an essential role in the transport workforce worldwide, working in formal and informal jobs in public transport, road freight and logistics, rail, maritime and aviation sectors, in ports and in active travel. Women, Work and Transport is an international collection that brings together researchers with global expertise in gender and transport work to provide original evidence of the experiences of women working in all transport modes across countries in the Global North and the Global South. The 21 chapters reveal the everyday challenges faced by women working in highly masculinised environments, including gender stereotypes about women's lack of suitability for transport work, gender-based violence and harassment, limited opportunities for promotion and progression, inflexible work patterns, poor working conditions, and lack of gender-specific facilities. The transport sector has also been severely affected by the coronavirus pandemic, resulting in widespread furlough and redundancies. The effect of the pandemic on women's work in transport is addressed, while other chapters also reveal how women have succeeded in transport occupations, with the support of mentoring schemes, leadership programmes and trade unions, highlighting new emerging opportunities to challenge occupational gender segregation as the transport sector transforms through automation, digitisation, and the transition to low-carbon technologies. The Transport and Sustainability series addresses the important nexus between transport and sustainability containing volumes dealing with a wide range of issues relating to transport, its impact in economic, social and environmental spheres, and its interaction with other policy sectors.
Keywords: Women transport workers.; Women -- Employment.; Transportation.; Sustainable development.; Business & Economics -- Industries -- Transportation.; Transport industries.; elektronické knihy; electronic books